Molecular Basis of the Antiangiogenic Action of Rosmarinic Acid, a Natural Compound Targeting Fibroblast Growth Factor‐2/FGFR Interactions. (6th November 2020) - Pagano, Katiuscia; Carminati, Laura; Tomaselli, Simona; Molinari, Henriette; Taraboletti, Giulia; Ragona, Laura
Abstract: Fibroblast growth factor (FGF2)/fibroblast growth factor receptor (FGFR) signalling plays a major role both in physiology and in several pathologies, including cancer development, metastasis formation and resistance to therapy. The development of small molecules, acting extracellularly to target FGF2/FGFR interactions, has the advantage of limiting the adverse effects associated with current intracellular FGFR inhibitors. Herein, we discuss the ability of the natural compound rosmarinic acid (RA) to induce FGF2/FGFR complex dissociation. The molecular‐level description of the FGF2/FGFR/RA system, by NMR spectroscopy and docking, clearly demonstrates that RA binds to the FGFR‐D2 domain and directly competes with FGF2 for the same binding site. Direct and allosteric perturbations combine to destabilise the complex. The proposed molecular mechanism is validated by cellular studies showing that RA inhibits FGF2‐induced endothelial cell proliferation and FGFR activation. Our results can serve as the basis for the development of new extracellular inhibitors of the FGF/FGFR pathways. Abstract : An asset in the antiangiogenic toolbox : Rosmarinic acid (RA) exerts an antiangiogenic action destabilising the complex of fibroblast growth factor‐2 (FGF2) with its receptor (FGFR). NMR spectroscopy and docking demonstrate that RA binds to the FGFR extracellular portion, competing with FGF2 for the same binding site, and induces allosteric effects. Cellular data prove RA inhibition of FGF2/FGFR signalling.